Gram-negative osteomyelitis: clinical and microbiological profile - Carvalho,Vladimir Cordeiro de (2012)
INTRODUCTION: Despite the growing interest in the study of Gram-negative bacilli (GNB) infections, very little information on osteomyelitis caused by GNB is available in the medical literature. OBJECTIVES AND METHODS: To assess clinical and microbiological features of 101 cases of osteomyelitis caused by GNB alone, between January 2007 and January 2009, in a reference center for the treatment of high complexity traumas in the city of São Paulo. RESULTS: Most patients were men (63%), with median age of 42 years, affected by chronic osteomyelitis (43%) or acute osteomyelitis associated to open fractures (32%), the majority on the lower limbs (71%). The patients were treated with antibiotics as inpatients for 40 days (median) and for 99 days (median) in outpatient settings. After 6 months follow-up, the clinical remission rate was around 60%, relapse 19%, amputation 7%, and death 5%. Nine percent of cases were lost to follow-up. A total of 121 GNB was isolated from 101 clinical samples. The most frequently isolated pathogens were Enterobacter sp. (25%), Acinetobacter baumannii (21%) e Pseudomonas aeruginosa (20%). Susceptibility to carbapenems was about 100% for Enterobacter sp., 75% for Pseudomonas aeruginosa and 60% for Acinetobacter baumannii. CONCLUSION: Osteomyelitis caused by GNB remains a serious therapeutic challenge, especially when associated to nonfermenting bacteria. We emphasize the need to consider these agents in diagnosed cases of osteomyelitis, so that an ideal antimicrobial treatment can be administered since the very beginning of the therapy.